An approach to improve implementation of PLM solution in food industry - case study of Poult Group. (2017) - Pinna, Claudia; Plo, Laureline; Robin, Vincent; Girard, Philippe; Terzi, Sergio
The food industry has a unique role in all countries' economies since it is essential to its people's health. This paper focuses on this important sector. The objective is to identify the main difficulties in the implementation phase of the product lifecycle management (PLM) solution in the design phase. It proposes an approach that could drive and support food companies to make specific and strategic decisions. This work starts with an analysis of the problems associated with the deployment of a PLM solution. Furthermore, this analysis allows the authors to propose an approach to select a PLM solution and to anticipate its deployment in a food company. The purpose of this approach is to increase the level of knowledge of the PLM solution in the food industry and to improve the new product development (NPD) process of the companies operating in the food industry. In this context, a specific industrial case (Poult case study) is described. In conclusion, this study gives a first theoretical framework which can help companies utilise PLM effectively by understanding the context in which they are positioned.